O mundo vivido à margem: espaço e lugar em contos de Chimamanda Ngozi Adichie - VIEIRA, Camila Cantanhede (2021)
The convergence of Geography with Literature allows the glimpse of a new perspective of understanding space as a fundamental element of literary narratives, in which the very geographical essence of being-in-the-world is expressed (DARDEL, 2011). The subjects' experiences, their life stories, anxieties and fears arising from their experiences in space, the details of a conflict and its meanings and senses are not exhausted in themselves, on the contrary, they extrapolate the contours of the fictional so that their themes achieve a certain universality. Thus, the present study has as its main objective the analysis of the short stories “A cela um” (“Cell one”), “Uma experiência privada” (“A private experience”) and “A embaixada americana” (“The American embassy”), by the Nigerian writer Chimamanda Ngozi Adichie, gathered in the book No seu pescoço (The thing around your neck), released in 2009 and translated into Portuguese in 2017. This research intends to investigate how, in African literature of English language, the Nigerian subject is related to his “lived geographical space”, from the perspective of experience, highlighting the categories space and place, spatiality and crowding, in addition to verifying the intricacies of the post-colonial condition of these literatures and their territorial and subjective implications in the literary work. Therefore, as a theoretical contribution to the analysis we propose, we will mobilize categories of Cultural Humanistic Geography, whose reflections are found in the work Space and Place: the perspective of experience (2013), and the reflections of authors who turn to the study and criticism of the post-colonial condition, such as Chinua Achebe and Inocência Mata. In the writing of Chimamanda Ngozi Adichie, it is possible to verify the articulation of the different ways in which the characters relate and perceive space. With an intense thematic and stylistic density and depth, Adichie, through his narrative, confirms that the topophilic feeling or its opposite, topophobia, shows behaviors and attitudes that disturb, crowd, and are sometimes confused with a false sense of freedom.